Pengaruh Lingkungan Belajar terhadap Minat Belajar Siswa pada Pembelajaran Pendidikan Agama Islam Kelas VIII di UPTD SMPN 3 Kecamatan Harau Kabupaten 50 Kota - Fitri J Fatmi S; Fenny Ayu Monia (Lembaga Yasin AlSys, 2026)
A conducive learning environment is a key factor in fostering students’ learning interest, particularly in Pendidikan Agama Islam (PAI; Islamic Religious Education). However, preliminary observations at UPTD SMPN 3 in Harau Subdistrict, 50 Kota Regency, revealed various learning environment problems, such as inadequate classroom conditions, noise, low levels of cooperation among students, and limited emotional closeness between teachers and students, all of which may reduce learning interest. This study aimed to analyze the effect of the learning environment on the learning interest of eighth-grade students in PAI lessons. A quantitative approach with a correlational design was employed, with a population of 140 eighth-grade students and a sample of 35 students selected using simple random sampling. Data were collected using a Likert-scale questionnaire and documentation, and were analyzed using the Kolmogorov–Smirnov normality test, linearity test, t-test, and coefficient of determination. The results show that the learning environment has a significant effect on students’ learning interest, as indicated by a calculated t-value of 2.948 greater than the critical t-value of 1.697 and a significance value of 0.003 < 0.05. The coefficient of determination (R²) of 0.347 indicates that the learning environment contributes 34.7% to students’ learning interest, while the remaining proportion is influenced by other factors beyond the scope of this study. The study concludes that a conducive learning environment plays an important role in enhancing students’ learning interest in PAI. The implications highlight the importance of the roles of teachers and schools in creating a comfortable, interactive learning environment that supports active student engagement to optimize learning interest and participation.